Modelo de Previsão do Potencial Eólico e Geração de Energia em Curto Prazo para Parques Eólicos - Ferreira, Adir A. B.; Goulart, Antônio G. O.; Sperandio, Mauricio; Moraes, Marcelo R.; Moreira, Davidson M. (Ciência e Natura, 2011)
.